Non-equilibrium plasma kinetics of CO2 in glow discharges: a comparison with existing modeling and experimental results. (1st October 2022) - Pietanza, L D; Colonna, G; Capitelli, M
Abstract: We report results obtained by our 0D, time-dependent self-consistent model for the description of the CO2 plasma kinetics in glow discharge conditions, comparing our results with the simulation and experimental results reported by Grofulovic et al (2018 Plasma Sources Sci. Technol. 27 115009; 2019 PhD Thesis ) and Klarenaar et al (2017 Plasma Sources Sci. Technol. 26 115008). Our model is based on the simultaneous solution of the kinetic equations describing the vibrational, the electronic excited states and the plasma chemistry and of the electron Boltzmann equation for the calculation of the electron energy distribution function (eedf). The results for the vibrational level densities of CO2 show a satisfactory agreement with the Grofulovic's model results, despite the differences in the vibrational energy level scheme and in the kinetic processes included with the correspondent rate coefficients, with a good match also with the corresponding experimental results. Moreover, conditions characterized by higher power density (5–50 W cm −3 ) have been investigated to understand the behavior of the CO2 plasma discharge when a higher vibrational excitation is present. Large deviations of the vibrational distributions of CO2 and CO from equilibrium ones are predicted both in discharge and post discharge conditions. In particular, the CO2 vibrational distribution presents a behavior similar to a Treanor distribution for v < 15 while a deactivation of the plateau in the vibrational distribution function after v > 15 appears as a consequence of the dissociation induced by vibrational excitation mechanism, i.e. pure vibrational mechanism, becoming important at higher power densities. Finally, the results dependence on the selection of the CO2 electron molecule dissociation cross section, i.e. Phelps (1973 J. Appl. Phys. 44 4464 or Cosby (1993 Report No. AD-A266 464 WL-TR-93-2004 (Dayton, OH: Wright-Patterson Airforce Base)), has been investigated, showing that its more opportune choice is still a problem to be discussed for the description of conditions in which the electron impact dissociation dominates the kinetics, while once vibrational excitation is activated, CO2 dissociation is essentially driven by vibrational-induced dissociation, depending to a minor extent from that choice.